Acute enhancement of jumping performance after different plyometric stimuli in high level gymnasts is associated with postactivation potentiation - Dallas, G. C.; Dallas, C. G.; Tsolakis, C. (Medicina dello Sport, 2019)
BACKGROUND: Limited research exists examining the effect of different type of plyometric exercises (typical vs. specialized) that are employed as part of warm-up or as a strength-power potentiating complex. Thus, the purpose of this study was to examine the effects of a typical and a specialized plyometric protocol on the occurrence of post-activation potentiation (PAP) effects on drop jump (DJ) performance. METHODS: Thirty-five high level male and female artistic gymnasts participated in this investigation. All participants performed a DJ before and after two different conditioning stimuli; the first consisted of 10 repetitions of a specific gymnastic exercise (Rondat) and the second consisted of 2 set of 5 repetitions of tuck jumps. DJ height, contact time and leg power were assessed before, immediately after and at 3, 6, and 9 min following the conditioning stimulus. RESULTS: DJ height enhanced significantly in post measurements in male and female gymnast (P<0.05). Further, DJ contact time was significantly different immediately after, and after 6 and 9 min after the intervention in males (P<0.05), but only immediately after and after 9 min in female gymnasts (P<0.05). Gymnasts of both gender responded in a similar way to the interventions with male gymnasts showing greater potentiating abilities in DJ height compared to females (P=0.001). CONCLUSIONS: The results of the present study support that high level gymnast must include similar protocols in the warm-up procedures in order to improve their jumping performance.